2017
DOI: 10.3390/ijerph14020198
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity and Plasma Glucose Level amongst Ellisras Rural Young Adult Males and Females: Ellisras Longitudinal Study

Abstract: Unhealthy lifestyle characteristics such as low physical activity (PA) and high plasma glucose levels (PGLs) may lead to the development of type 2 diabetes mellitus in adulthood. The aim of this study was to investigate (i) the level of physical activity; (ii) the prevalence of pre-diabetes and (iii) the relationship between PA and plasma glucose level in a rural Ellisras adult population aged 18 to 28 years. A total of 713 young adults (349 males and 364 females) who took part in the Ellisras Longitudinal Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Meanwhile, IPAQ long forms cover 4 domains including work-related activities, transportation, housework and gardening, and leisure time. 1,12 Physical activity improves energy balance and prevents obesity which is an independent risk factor of prediabetes. Physical activity reduces blood glucose and increases insulin sensitivity in DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, IPAQ long forms cover 4 domains including work-related activities, transportation, housework and gardening, and leisure time. 1,12 Physical activity improves energy balance and prevents obesity which is an independent risk factor of prediabetes. Physical activity reduces blood glucose and increases insulin sensitivity in DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Amsterdam, Kemper et al [29] reported a clear increase in prevalence of obesity from youth to adulthood with a decrease in physical activity. However, undernutrition and low physical activity was high in the Ellisras rural population [30,31]. This might indicate that undernutrition as an indicator of NCD could be the cause of death or leads to permanent loss of follow-up of the ELS participants.…”
Section: Discussionmentioning
confidence: 95%
“…16 Today, from the same ELS sample measured from November to December 2015, the prevalence of obesity is high, particularly among the females. 17 Furthermore, it was clear from the previous analysis of this population that the prevalence of hypertension was emerging and low. 13,18 Currently, the prevalence of diabetes and hypertension are escalating in this Ellisras population.…”
Section: Ellisras Longitudinal Study Projectmentioning
confidence: 89%